Children with social anxiety disorder show blunted pupillary reactivity and altered eye contact processing in response to emotional faces: Insights from pupillometry and eye movements. (August 2018) - Keil, Verena; Hepach, Robert; Vierrath, Severin; Caffier, Detlef; Tuschen-Caffier, Brunna; Klein, Christoph; Schmitz, Julian
Highlights: Children with different anxiety disorders showed biases in eye contact processing. Blunted pupillary reactivity only in children with social anxiety disorder. Disorder-specific and transdiagnostic processes are relevant for childhood anxiety. Abstract: Cognitive models and adult research associate social anxiety disorder (SAD) with hypervigilant-avoidant processing of social information, such as eye contact. However, processing biases in childhood SAD remain mostly unexplored. We examined 10- to 13-year-old children's eye contact processing and pupil dilation in response to happy, neutral, and angry faces in three groups: SAD ( n  = 31), mixed anxiety disorders (MAD; n  = 30), and healthy controls (HC; n  = 32). Compared to HC, SAD children showed faster first fixations on the eye region of neutral faces and shorter first fixation durations on the eye region of all faces. No differences between the two clinical groups emerged in eye movement results. SAD girls showed reduced pupil dilation in response to happy and angry faces compared to MAD and to happy faces compared to HC. SAD boys showed reduced pupil dilation in response to neutral faces compared to HC. Dimensionally, reduced pupil dilation was linked to social anxiety severity while eye movements were correlated with mixed anxiety and depressive severity. Results suggest that hypervigilant-avoidant eye contact processing and a blunted pupillary reactivity characterize children with SAD. Both transdiagnostic and disorder-specific processing biases are relevant for the understanding of childhood SAD.